Exposure to chlorantraniliprole reduces locomotion, respiration, and causes histological changes in the midgut of velvetbean caterpillar Anticarsia gemmatalis (Lepidoptera: Noctuidae). (January 2021) - Castro, Bárbara Monteiro de Castro e; Martínez, Luis Carlos; Plata-Rueda, Angelica; Soares, Marcus Alvarenga; Wilcken, Carlos Frederico; Zanuncio, Antônio José Vinha; Fiaz, Muhammad; Zanuncio, José Cola; Serrão, José Eduardo
Abstract: The anthranilic diamide, chlorantraniliprole is a systemic insecticide affecting ryanodine receptors. This insecticide is used to control caterpillars in soybean crops because it has low toxicity to non-target organisms. The objective was to identify side-effects of chlorantraniliprole on midgut histopathology, respiration and behavior of the velvetbean caterpillar Anticarsia gemmatalis in laboratoty. Chlorantraniliprole has LC50 = 0.61 (0.58–0.64) mg mL −1 for A. gemmatalis fourth instar caterpillars after 96 h. The insecticide causes severe histopathological effects in the midgut with epithelial disorganization, microvilli degeneration, cytoplasm vacuolization, cell fragmentation, and peritrophic matrix disorganization. The respiratory rate and the walking speed decrease, whereas the resting period increase for caterpillars exposed to this insecticide. Chlorantraniliprole is toxic to A. gemmatalis at median lethal concentrations causing severe histological and ultrastructural changes with degeneration of the midgut epithelium, reduction of respiratory rates and inducing an arresting behavioral response of this insect. Highlights: Effective dominance of resistance of Anticarsia gemmatalis to insecticides and bioinsecticides have been reported in Brazil. The insecticidal effects of the anthranilic diamide chlorantraniliprole were tested on A. gemmatalis. Chlorantraniliprole was toxic to S. frugiperda at different lethal and sublethal concentrations. Chlorantraniliprole exhibited significant activity to altering the locomotor activity and reducing the respiration rate. Lethal and sublethal effects of chlorantraniliprole in A. gemmatalis can be an alternative to control for this pest.